2018
DOI: 10.3389/fpls.2018.01115
|View full text |Cite
|
Sign up to set email alerts
|

Faba Bean Cultivation – Revealing Novel Managing Practices for More Sustainable and Competitive European Cropping Systems

Abstract: Faba beans are highly nutritious because of their high protein content: they are a good source of mineral nutrients, vitamins, and numerous bioactive compounds. Equally important is the contribution of faba bean in maintaining the sustainability of agricultural systems, as it is highly efficient in the symbiotic fixation of atmospheric nitrogen. This article provides an overview of factors influencing faba bean yield and quality, and addresses the main biotic and abiotic constraints. It also reviews the factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 174 publications
(202 reference statements)
7
106
0
6
Order By: Relevance
“…In the flowering stage (BBCH 63-69), seed yield was considerably affected by precipitation total of 20-25 mm/m 2 and temperature of 16-18 • C. According to Fahad [18], suboptimal water supply and temperatures exert adverse effects on plant growth and yields. Karkanis [26] reported that climate change is also gradually affecting many European regions, so it is imperative to breed elite cultivars that feature a higher abiotic and biotic stress resistance and nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…In the flowering stage (BBCH 63-69), seed yield was considerably affected by precipitation total of 20-25 mm/m 2 and temperature of 16-18 • C. According to Fahad [18], suboptimal water supply and temperatures exert adverse effects on plant growth and yields. Karkanis [26] reported that climate change is also gradually affecting many European regions, so it is imperative to breed elite cultivars that feature a higher abiotic and biotic stress resistance and nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…However, these types of studies are still not conclusive as the effect of legume consumption on human health seems to be dependent on the type, amount, and frequency of legume consumption, and they also do not consider the effects of processing [35]. In the environment, legumes are part of the symbiotic N fixation process, reducing the need for N fertilizer, decreasing agricultural CO 2 emissions, and improving soil composition [37]. The inclusion of legumes in crop rotation systems, besides conferring pest and disease resistance to the succeeding crops [38], can reduce greenhouse gas emissions by up to 25% [39].…”
Section: The Importance Of Legumes In the Accomplishment Of The Sustamentioning
confidence: 99%
“…Faba bean maintains the sustainability of agricultural systems due to efficient symbiotic fixation of atmospheric nitrogen (Karkanis et al 2018). According to the Ntatsi et al (2018) investigations, the total amount of biologically fixed N in faba bean crop varied from 118.5 to 193.9 kg ha −1 depending on the various cropping systems and cultivars.…”
Section: Introductionmentioning
confidence: 99%